Characterisation of industrially produced galvannealed coating by open circuit potential (OCP) measurement technique. (2nd November 2018) - Manna, M.
ABSTRACT: An attempt has been made to characterise the industrially produced galvannealed coating by the open circuit potential (OCP) measurement technique. It confirms that the industrially produced galvannealed coating consists of four iron–zinc intermetallic phases, Fe3Zn10, Fe5Zn21, FeZn10 and FeZn13, in layers on the steel substrate. The OCP results are compared with other characterisation techniques such as galvanostatic scan EIS and glow discharge optical emission spectroscopy (GDOES). The additional advantage of this technique is not only to confirm different iron–zinc intermetallic phases in the coating but also to identify the stability of all these phases in an aggressive chloride environment. It was established that the dissolution rate of the Fe3Zn10 phase which contains the maximum amount of iron is the slowest whereas the dissolution rate of the FeZn13 phase which contains the minimum amount of iron is the fastest. This can be explained by the fact that the phase containing more of the more active metal (zinc) is dissolved faster than the phase containing more of the less active metal (iron).